Study of notch effect on the mechanical properties of modern gas pipeline - Manikam, Ravindran (2012)
This paper presents analysis of different sizes of notch effect on the smooth tensile round bar of gas pipe by using finite element analysis for API X65 steel. The damage consider on the pipe is a third party accidents which means casual defect occurs after the fabrication or during the installation. Based on detailed finite element (FE) analyses the result stress strain curve compare among the notch radius of 6mm, 3mm, 1.5mm and also with smooth simulation model. The analysis carried on the high strength steel of API X70 and API X100 and compare with API X65. The result from the analysis is when the notch radius decreases yield and tensile strength increases but strain to the fracture decreases. The yield strength and tensile strength for the smooth and notch effect are greater for API X70 followed by API X100 compare with API X65.